2018
DOI: 10.1186/s13058-018-1017-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and breast cancer association according to menopausal status and body mass index

Abstract: BackgroundThyroxine (T4) has been positively associated with tumor cell proliferation, while the effect of triiodothyronine (T3) on cell proliferation has not been well-established because it differs according to the type of cell line used. In Mexico, it has been reported that 14.5% of adult women have some type of thyroid dysfunction and abnormalities in thyroid function tests have been observed in a variety of non-thyroidal illnesses, including breast cancer (BC). These abnormalities might change with body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 85 publications
4
26
0
Order By: Relevance
“…We found that the association between thyroid function and incident breast cancer did not significantly differ by obesity among premenopausal and postmenopausal women. It is difficult to directly compare our findings with previous studies because we used FT4 serum concentration while previous studies used TT4 . Only a previous study by Ortega‐Olvera et al evaluated the effect modification by obesity in premenopausal and postmenopausal women and demonstrated that effect of TT4 on breast cancer increased as BMI increased in postmenopausal women .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We found that the association between thyroid function and incident breast cancer did not significantly differ by obesity among premenopausal and postmenopausal women. It is difficult to directly compare our findings with previous studies because we used FT4 serum concentration while previous studies used TT4 . Only a previous study by Ortega‐Olvera et al evaluated the effect modification by obesity in premenopausal and postmenopausal women and demonstrated that effect of TT4 on breast cancer increased as BMI increased in postmenopausal women .…”
Section: Discussionsupporting
confidence: 70%
“…31 Only a previous study by Ortega-Olvera et al evaluated the effect modification by obesity in premenopausal and postmenopausal women and demonstrated that effect of TT4 on breast cancer increased as BMI increased in postmenopausal women. 31 This finding is in line with our finding but in the present study, we could not reach significant conclusion due to insufficient outcome events despite relatively large sample size. Several mechanisms have been hypothesized to explain the association between thyroid hormones and breast carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in cases of benign thyroid disease, elevated serum thyroid-stimulating hormone (TSH) or triiodothyronine (T3) independently or in combination with estrogen, have been associated with a higher rate of BC and more rapid cancer progression in some studies (4)(5)(6). A meta-analysis of multi-national trials have demonstrated that BC is the most common secondary malignancy in female patients with thyroid cancer (6,7), and BC patients have a significantly higher risk of thyroid cancer; thus the relationship appears to be hormonal in nature and bidirectional (7)(8)(9). Preclinical models and in Research.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, again both hyperthyroidism and hypothyroidism have been shown to influence cancer onset in both directions and thus no clear consensus exists. As this goes beyond the scope of the current review, please refer to recent studies and reviews for more information on the subject (Hellevik et al 2009, Khan et al 2016, Chan et al 2017, Ortega-Olvera et al 2018reviewed in Hercbergs et al 2010, Moeller & Führer 2013.…”
Section: Thyroid Hormone Status and Cancer Survivalmentioning
confidence: 99%